Video Teaser Batik Edu-Tourism Sebagai Promosi Iconic Pariwisata Kota Pekalongan - Wenti Ayu Sunarjo; Victorianus Aries Siswanto; Amalia Ilmiani (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2021)
This research produces information products about Pekalongan city batik educational tourism packaged in audio-visual form with the aim of increasing Pekalongan City's daytime power through audio-visual promotional media innovations that carry the concept of educational travel on the local wisdom product